Regulatory T Cells Diminish HIV Infection in Dendritic Cells – Conventional CD4+ T Cell Clusters - Moreno-Fernandez, Maria E.; Joedicke, Jara J.; Chougnet, Claire A. (Frontiers in Immunology, 2014)
Formation of immunological synapses between dendritic cells (DC) and conventional CD4+ T cells (Tcon) is critical for productive immune responses. However, when DCs are HIV-infected such synapses are critical to establish HIV infection. As regulatory T cells (Treg) control DC-Tcon interactions, we inquired whether Treg might interfere with DC to Tcon HIV transmission. We developed a model, using monocyte-derived DC infected with R5-HIV, and cultured with Tcon in the presence or absence of autologous Treg, using the physiological ratio of 1 Treg for 10 Tcon. Cultures containing Treg significantly decreased HIV transmission from DC to T cell. Notably, the IS was a focus of this interference as Treg decreased actin polymerization and IS formation, but minimally affected DC activation. Importantly Treg decreased the trafficking of HIV punctate to the IS. Further, CD152 and cyclic adenosine monophosphate were critical Treg effector molecules, as their individual or simultaneous blockade abolished Treg activity, however no additive effect was found. Together, these data suggest that Treg can reduce HIV dissemination, which may be beneficial to the host in the early stages of infection.